Strategies for improving english learning in sixth course students at Carlos Cueva Tamariz high school - Chica Cárdenas, Yola Indaura
This work investigates the improvement in English performances of 43 sixth course students at Carlos Cueva T. high school. These students were not motivated to learn English and had a very low English level. To face this problem and considering students´ interests and needs, a variety of strategies were planned. Among these strategies, the enhancement of motivation in the classroom, the teaching of learning strategies and the stress on indirect strategies were adopted and applied by the teacher. The goal of these strategies was to help the students overcome the difficulties they faced in the learning of English. All these strategies were applied in a certain period of time and data was collected from different sources. After the application of the mentioned strategies, the students changed their attitudes towards the target language and consequently, they improve their English level. Moreover, it was demonstrated that motivation is a really important factor that positively influences the learning of English, and this factor does not occur in isolation but is interrelated with social and cultural aspects that strongly influence the learning process.